Endearing Empress Cixi : re-empowering Asian identities and re-evaluating western ideologies in Dick Lee’s "Forbidden city : portrait of an empress". - Ho, Terence Kin Wai. (2012)
This essay explores the dilemmas behind Empress Cixi’s personality, as well as the underlying relationship and tension between the East and the West. In his musical, Lee sets out to challenge the pre-conceived notions of Empress Cixi as a Dragon Lady who ruled China with an iron fist and eventually brought about its downfall. He ultimately projects Yehenara (Empress Cixi’s maiden name) as a sentimental and softhearted woman, as well as a loving mother, who is truly unlike who she is thought or said to be. In this sense, Lee shifts the focus of the highly detestable Empress Cixi, to an endearing character who is impaired by the West. This paper will show how Lee utilizes the misinterpreted character of Empress Cixi to criticize the increasing emphasis on a global, and more strictly, a Westernized culture and association, at the expense of forgoing a collective Asian identity. It will also highlight Lee’s attempts in employing Empress Cixi’s sensitivity to restructure the traditional perceptions and prejudices of the Empress, so as to re-empower and reinstate a pride and belief in an Asian identity that is not subservient to the ideologies of the West.